Impact Of Altitude On Insect Pest Occurrence In Mandarin (Citrus reticulata Blanco) Orchards Within Jajarkot District - Ghimire, Roshan; Dhakal, Astha; Karkee, Suraj Singh; Acharya, Sapana (Nepalese Horticulture, 2024)
An experiment was conducted to assess the pest status and effect of altitude on insect pests of mandarin orchards from April to June 2023 at Kushe rural municipality, Jajarkot, Nepal, located within the Citrus Zone under PMAMP. The experiment comprised five different altitude ranges as treatments: 1400-1500 masl, 1500-1600 masl, 1600-1700 masl, 1700-1800 masl, and 1800-1900 masl. Sample data were collected through visual observation and monitoring using yellow sticky traps. The research employed a randomized complete block design with five treatments and five replications. Data analysis was conducted using R (version 4.3.1) and MS-Excel. The study identified citrus leaf miners (Phyllocnistic citrella) and fruit flies (Bactrocera tau) as major threats in mandarin orchards in Jajarkot. Likewise, scale insects (Aonidela auranti), aphids (Toxoptera spp), whiteflies (Dialeurodes citi), lemon butterflies (Papilio demoleus), citrus tree borer (Chilodonium cinctum), red citrus mites (Panonychus citri), red ants (Oecophylla smaragdina), citrus green stink bugs (Rhynhocoris humeralis), and mealybugs (Planococcus citri) were present in minority. The results showed that there is a significant effect of altitude on the percentage of leaf damage caused by citrus leaf miners (P<0.001), and the number of trapped fruit flies (p<0.01), aphids (P<0.01), and whiteflies (P<0.01). However, altitude showed a non-significant effect on scale insect incidence. All pests except scale insects were more abundant at lower altitudes, with the highest occurrence at 1400-1500 masl and the lowest at 1800-1900 masl. Mealybugs, red citrus mites, and citrus tree borer damage were not seen at altitudes above 1800 masl. This study highlights altitude as a key factor in pest occurrence.